2016
DOI: 10.1182/blood-2015-09-670950
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of fresher vs older red blood cells in hospitalized patients: a systematic review and meta-analysis

Abstract: The impact of transfusing fresher vs older red blood cells (RBCs) on patientimportant outcomes remains controversial. Two recently published large trials have provided new evidence. We summarized results of randomized trials evaluating the impact of the age of transfused RBCs. We searched MEDLINE, EMBASE, CINAHL, the Cochrane Database for Systematic Reviews, and Cochrane CENTRAL for randomized controlled trials enrolling patients who were transfused fresher vs older RBCs and reported outcomes of death, adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
80
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 57 publications
1
80
2
5
Order By: Relevance
“…The median [interquartile range] storage time of and 15 [11][12][13][14][15][16][17][18][19][20] days in fresh blood and in old blood groups, respectively. The occurrence of postoperative infection did not differ between groups (fresh blood 22% vs. old blood 25%; relative risk [RR], 1.17; confidence interval [CI], 0.71-1.93), although wound infections occurred more frequently in old blood (15% vs. 5%; RR, 3.09; CI,).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median [interquartile range] storage time of and 15 [11][12][13][14][15][16][17][18][19][20] days in fresh blood and in old blood groups, respectively. The occurrence of postoperative infection did not differ between groups (fresh blood 22% vs. old blood 25%; relative risk [RR], 1.17; confidence interval [CI], 0.71-1.93), although wound infections occurred more frequently in old blood (15% vs. 5%; RR, 3.09; CI,).…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors reported that the results are difficult to interpret because the studies involved different populations and there were considerable differences in the length of storage of fresh and old blood and in study methods. 15 To our knowledge, the association of age of RBCs with infections in noncardiac surgery population has not been investigated by double-blind randomized studies. Accordingly, the aim of this study was to investigate the relationship between RBC storage time and postoperative infection after elective noncardiac surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, RCTs also could not demonstrate adverse effects of aged RBC transfusions on mortality or organ failure compared to fresh RBC transfusions. 26,27 Although using allogeneic RBC transfusions to achieve a hemoglobin target of >9 g/dL appears to be relatively safe for most critically ill patients, this does not imply allogeneic RBCs are totally safe for all critically ill patients.…”
mentioning
confidence: 99%
“…19,20 A recent meta -analysis and systematic review has indicated that the current evidence provides moderate certainty that use of fresher RBCs does not influence mortality, and low certainty that it does not influence adverse events but could possibly increase infection rates. 21 In addition, handling of the blood products greatly influences the quality of both the shorter-and the longer -stored RBC units. Once issued by the blood bank, the transfusion of RBC units should be commenced within 30 minutes of removal from the optimal storage conditions.…”
mentioning
confidence: 99%